2014
DOI: 10.1038/hr.2014.161
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum uric acid levels and the incidence of hypertension and metabolic syndrome: a 4-year follow-up study of a large screened cohort in Okinawa, Japan

Abstract: The purpose of this study was to examine the associations between serum uric acid (SUA) levels and the incidences of hypertension and metabolic syndrome (MetS) in a large screened cohort of Japanese men and women. We evaluated 4812 subjects (males, 2528; females, 2284; mean age, 47.5 years) who underwent health checkups between 2006 and 2010 and were free of hypertension and MetS in 2006. After 4 years, 618 (13%), 764 (16%) and 158 (3%) subjects developed hypertension, MetS and hypertension with MetS, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Obesity, insulin resistance, type 2 diabetes, and hyperlipidemia are all recognized risk factors for NAFLD (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Similarly, an association between elevated serum uric acid levels and the prevalence or incidence of the metabolic syndrome or its features such as hypertension, insulin resistance, diabetes, dyslipidemia, and obesity was repeatedly demonstrated in several studies (12,13,(45)(46)(47). However, it is presently not clear whether the association between uric acid and NAFLD is independent of obesity and metabolic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, insulin resistance, type 2 diabetes, and hyperlipidemia are all recognized risk factors for NAFLD (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Similarly, an association between elevated serum uric acid levels and the prevalence or incidence of the metabolic syndrome or its features such as hypertension, insulin resistance, diabetes, dyslipidemia, and obesity was repeatedly demonstrated in several studies (12,13,(45)(46)(47). However, it is presently not clear whether the association between uric acid and NAFLD is independent of obesity and metabolic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as glucose, total cholesterol, highdensity lipoprotein cholesterol, 31 uric acid, 32 smoking, body mass index and triglycerides 33 were also selected for inclusion in the fully adjusted model that considered these factors correlated with blood pressure levels in former studies but that were not included in the list of covariates. These factors were included into the fully adjusted model but did not distinctly alter the association of elevated MPV and the increased risk of hypertension.…”
Section: Mpv and Hypertension L Gang Et Almentioning
confidence: 99%
“…In fact, several epidemiological studies have shown that hyperuricemia is associated with hypertension, cardiovascular disease and metabolic syndrome [Nagahama et al 2015]. Approximately 25% of patients with hypertension have hyperuricemia, while approximately 30% of patients with hyperuricemia or gout suffer hypertension [Nishida et al 2013].…”
Section: Introductionmentioning
confidence: 99%